Very low isotope ratio of iron in fine aerosols related to its contribution to the surface ocean. Issue 18 (28th September 2016) - Kurisu, Minako; Takahashi, Yoshio; Iizuka, Tsuyoshi; Uematsu, Mitsuo
Abstract: Seven size‐fractionated aerosol samples were collected from Hiroshima, Japan, and were analyzed in terms of chemical composition, soluble fraction of iron (Fe), Fe species, and Fe isotope ratios. The results suggested that Fe in fine particles contained a larger fraction of anthropogenic aerosols than coarse particles did. Iron in the fine particles was more soluble in simulated seawater (up to 25%) than that in the coarse particles and was in the form of Fe (hydr)oxide species, such as ferrihydrite or hematite. The Fe isotope ratios (δ 56 Fe) of the coarse particles (+0.04‰ to +0.30‰) were close to the crustal mean value (0.0‰). By contrast, the δ 56 Fe values of fine particles were much lower and ranged from −2.01‰ to −0.56‰. δ 56 Fe values of the soluble Fe fraction in the fine particles were remarkably low (−3.91 to −1.87‰), suggesting that anthropogenic aerosols yield soluble Fe with low δ 56 Fe values. Such low values could be explained by kinetic isotope fractionation during evaporation of Fe at high temperatures, coupled with the refractory characteristics of Fe. Marine aerosols from the Northwest Pacific were also analyzed. The δ 56 Fe values in the fine particles were also lower than those in the coarse particles. These results may be important to quantitatively estimate the contribution of anthropogenic Fe deposited on the surface ocean on the basis of the Fe isotopes. Key Points: Lower isotope ratios were detected for iron in fine aerosols than in coarse aerosols Rayleigh isotope fractionation is a possible explanation for the low isotope ratio Input of anthropogenic Fe in aerosols should be considered when modeling the Fe isotope budget in surface ocean